Changes to the Editorial Board - Del Alamo, Jesus A. (IEEE electron device letters, 2022)
It is my pleasure to welcome Dr. Xiao Gong to the Editorial Board of IEEE Electron Device Letters. A biography and picture of Dr. Gong can be found below. His subject areas are compound semiconductor devices, optoelectronics, display, imaging, thin-film transistors, ferroelectric memories, and silicon and column IV semiconductor devices.